Co-crystallisation as a modular approach to the discovery of spin-crossover materials. Issue 11 (24th February 2022) - Birchall, Lee T.; Truccolo, Giada; Jackson, Lewis; Shepherd, Helena J.
Abstract : The switching behaviour of spin crossover cocrystals can be modified through changing the coformer and thus co-crystallisation presents a rapid, facile and highly modular tool for the discovery of new switchable materials. Abstract : Herein we present co-crystallisation as a strategy for materials discovery in the field of switchable spin crossover (SCO) systems. Using [Fe(3-bpp)2 ]·2A (where 3-bpp = 2, 6-bis(pyrazol-3-yl)pyridine, A = BF4 − /PF6 − ) as a starting point, a total of 11 new cocrystals have been synthesised with five different dipyridyl coformers. Eight of these systems show spin crossover behaviour, and all show dramatically different switching properties from the parent complex. The cocrystals have been studied by variable temperature single-crystal X-ray diffraction and SQUID magnetometry to develop structure–property relationships. The supramolecular architecture of the cocrystals depends on the properties of the coformer. With linear, rigid coformer molecules leading to 1D supramolecular hydrogen-bonded chains, while flexible coformers form 2D sheets and bent coformers yield 3D network structures. The SCO behaviour of the cocrystals can be modified through changing the coformer and thus co-crystallisation presents a rapid, facile and highly modular tool for the discovery of new switchable materials. The wider applicability of this strategy to the design of hybrid multifunctional materials is also discussed.